Airport quality assessment: combination of Servqual and Kano model - Silva, Peri Guilherme Monteiro da (Brazilian Journal of Production Engineering, 2025)
Service quality assessment is a key strategic element for the competitiveness and sustainability of organizations. This study combines the SERVQUAL and Kano models to identify opportunities for improving user perception regarding services provided at an airport in the state of Pará, Brazil. SERVQUAL allows for the measurement of gaps between users’ expectations and actual service perceptions, while the Kano model categorizes service attributes based on their impact on satisfaction. Questionnaires were administered between August and November 2024 to a random sample of 50 users. The findings highlight that users place great importance on clear information about service schedules, empathetic and well-trained staff in problem resolution, and the perception that their interests are acknowledged as relevant. The main conclusion indicates that improving service quality, from the users’ perspective, requires a focus on understanding their needs, demonstrating empathy, and ensuring that staff convey trust and confidence when providing information. This study contributes to the academic literature by integrating two complementary methodologies for evaluating service quality and demonstrating their applicability in the airport sector.